2011
DOI: 10.1089/vbz.2010.0276
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction Confirmation ofBabesia canis canisandAnaplasma phagocytophilumin Dogs Suspected of Babesiosis in Slovakia

Abstract: Canine babesiosis was considered an imported tick transmitted disease until the first case of autochthonous canine babesiosis in Slovakia was described in 2002. Since then, the number of cases kept increasing every year. The causative agent of babesiosis in dogs is not yet characterized; therefore, the aim of our study was to determine the agent and the rate of infection in the vector tick D. reticulatus in Slovakia. Babesia canis canis was detected in 80 out of 87 blood samples from dogs with clinical manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…M'Ghirbi & Bouattour (2008) obtained a prevalence of 0.6% in Tunisia. Higher prevalence was found in 35.6% ticks in Slovakia (Majláthová et al 2011).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…M'Ghirbi & Bouattour (2008) obtained a prevalence of 0.6% in Tunisia. Higher prevalence was found in 35.6% ticks in Slovakia (Majláthová et al 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Detection of Babesia infection in ticks has been widely used in epidemiological studies in various countries , Matjila et al 2005, M'Ghirbi & Bouattour 2008, Majláthová et al 2011. However, in Brazil, few studies have been performed and little is known about the aspects of infection with Babesia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In BLAST Majlathova et al 2011;Kubelova et al 2013). B. canis was previously reported from the CR; however, all cases were in dogs with a history of travel to endemic areas (Kucera 1992;Svobodova and Svobodova 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, one can assume that the spread of B. canis follows the natural distribution of its vector. However, the data on B. canis infection in dogs or ticks in areas of Slovakia and Austria adjacent to the borders of the Czech Republic are either absent, or infection was Majlathova et al 2011;Kubelova et al 2013;Halos et al 2014;Pantchev et al 2015). Recent phylogenetic studies suggested intraspecies diversity of B. canis.…”
Section: Resultsmentioning
confidence: 99%
“…Canine babesiosis caused by B. canis is considered an emerging disease spreading with its vector Dermacentor reticulatus (Fabricius) (Zygner et al 2009). Clinical cases of babesiosis caused by B. canis are milder and have been reported from countries neighbouring with the Czech Republic, such as Austria, Germany, Poland and Slovakia (Zahler et al 2000, Chandoga et al 2002, Adaszek and Winiarczyk 2008, Majláthová et al 2011, Silaghi et al 2011). The more pathogenic B. gibsoni has been recently reported from Slovakia (Víchová et al 2016).…”
mentioning
confidence: 99%